2019
DOI: 10.1039/c9ra01479a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient & stable Bi & Sb anodes using lithium borohydride as solid electrolyte in Li-ion batteries

Abstract: All solid-state Li-ion batteries using commercial Bi and Sb as negative electrodes with a high coulombic efficiency (90–99%) and high capacity retention of 82 and 95%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Several reports stated that the cyclic stability of Bi-based electrodes remained less than 300 mAhg −1 after 100 cycles [55][56][57][58]. These lower capacity and cyclic stability issues were solved by the implementation of Bi anode in all-solid-state Li-ion batteries [59]. Jain and co-workers did excellent work in this regard.…”
Section: Development Of Bi-based Anodes For Li-ion Batteriesmentioning
confidence: 99%
See 3 more Smart Citations
“…Several reports stated that the cyclic stability of Bi-based electrodes remained less than 300 mAhg −1 after 100 cycles [55][56][57][58]. These lower capacity and cyclic stability issues were solved by the implementation of Bi anode in all-solid-state Li-ion batteries [59]. Jain and co-workers did excellent work in this regard.…”
Section: Development Of Bi-based Anodes For Li-ion Batteriesmentioning
confidence: 99%
“…Details of all-solid-state Li-ion batteries (ASSLIBs) are already discussed in the introduction section. They These lower capacity and cyclic stability issues were solved by the implementation of Bi anode in all-solid-state Li-ion batteries [59]. Jain and co-workers did excellent work in this regard.…”
Section: Development Of Bi-based Anodes For Li-ion Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…8 A similar cushioning effect was also observed in our recent report where a hydride based solid electrolyte -LiBH 4 was used with Bi (as an anode) to assemble an all-solid-state battery and the obtained results showed that the existence of LiBH 4 as well as acetylene black (AB) impressively improved the cyclability of Bi anode. 9 In order to further enhance the capacity, Bi based chalcogenides (Bi 2 X 3 ; X ¼ S, Se, Te) have been explored, as the element X has ability to alloy with Li. 10,11 Out of these chalcogenides, Bi 2 S 3 possesses highest capacity and in addition to Li-ion batteries it has been widely used in many elds, such as optics, 12,13 photoelectricity, 14,15 photocatalysis 16,17 and biology 18,19 due to its direct band gap (1.3 eV).…”
Section: Introductionmentioning
confidence: 99%